Reversible chemical reactions for single-color multiplexing microscopy - Brox, Dominik; Schwering, Michael; Engelhardt, Johann; Herten, Dirk-Peter (ChemPhysChem, 2014)
Abstract Recent developments in biology demand an increasing number of simultaneously imaged structures with standard fluorescence microscopy. However, the number of multiplexed channels is limited for most multiplexing modalities, such as spectral multiplexing or fluorescence-lifetime imaging. We propose extending the number of imaging channels by using chemical reactions, controlling the emissive state of fluorescent dyes. As proof of concept, we reversibly switch a fluorescent copper sensor to enable successive imaging of two different structures in the same spectral channel. We also show that this chemical multiplexing is orthogonal to existing methods. By using two different dyes, we combine chemical with spectral multiplexing for the simultaneous imaging of four different structures with only two spectrally different channels. We characterize and discuss the approach and provide perspectives for extending imaging modalities in stimulated emission depletion microscopy, for which spectral multiplexing is technically demanding.
Gesehen am 27.08.2020